Structural control and fault detection of wind turbine systems - Karimi, Hamid Reza (IET energy engineering series ;, 2018)
With the rapid growth of wind energy worldwide, challenges in the operation and control of wind turbine systems are becoming increasingly important. These affect all parts of the system, and require an integrated approach to optimize safety, cost, integrity and survivability of the system, while retaining the desired performance quality. This book conveys up to date theoretical and practical techniques applicable to the control of wind turbine systems. Topics covered include wave loads on monopole-supported offshore wind turbines; numerical and experimental tools for small wind turbine load analysis; structural control concepts for load reduction of offshore wind turbines; towards farm-level health management of wind turbine systems; data-based approaches to the monitoring of wind turbines; fault diagnostics for electrically operated pitch systems in offshore wind turbines; an emulator prototype design for vibration control of magnetic bearings for wind turbine power generator shafts; condition monitoring and diagnostics of wind turbine power trains; and robust fuzzy fault tolerant control wind energy systems subject to actuator and sensor faults.